Description of two new species of the genus Scaphomonus Viraktamath, 2009 (Hemiptera: Cicadellidae: Deltocephalinae) from China - Duan, Keting; Xing, Jichun (Zootaxa, 2024)
Two new leafhopper species: Scaphomonus digitatus sp. nov. and S. sinuatus sp. nov. are described and illustrated from Yunnan Province, China. A key to the Chinese species of the genus is given. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).